(untitled) (TAJ: Journal of Teachers Association, 2018)
Tennis elbow is a common and well defined clinical entity. It is an extra articular affection characterised by pain and acute tenderness at the origin of the mainly extensorcarpi radialis brevis, but can involve the tendons of the extensorcarpi radialis longus and the extensor digitorum communis. It is also called lateral epicondylitis. Various types of treatment option for this disease that is conservative and operative. An injection of autologus blood might provide the necessary cellular and humoral mediators to induce a healing cascade. The purpose of the study was to evaluate result of epicondylitis treated with autologus blood injection.Total 19 patients with tennis elbow treated in this study.Among the patients 9 were male and 10 were female.Age of the patients were 25yrs – 60yrs, average 41.63yrs. All patients had failed previous non-surgical treatment. Duration of the pain 1 month to 6 months. All the patients got autologus blood injected every 21 days interval (one or three times). Before autologus blood injection average pain score was 6.2 and average Nirschi score was 5.8. After autologus blood injection pain score and Nirschi score decreases 2.2 and 2 respectively. Average follow-up period was 7 months. TAJ 2013; 26: 79-81